Computational models in biomedical engineering : finite element models based on smeared physical fields : theory, solutions, and software /: finite element models based on smeared physical fields : theory, solutions, and software. (2022) - Kojic, Milos, 1941-; Milosevic, Miljan; Ziemys, Arturas
No abstract available